Application of Foot Massage Therapy to Reduce Blood Pressure in Elderly Hypertension - Meylia, Indah Puspita; Iswantiningsih, Elisabeth; Daruwati, Christiana Endang (Global Health Science Group, 2024)
Hypertension is a disease that many Indonesian people suffer from because the prevalence of hypertension cases in Indonesia especially the elderly is the third highest in the world. Management of hypertension is divided into two, namely pharmacological and non-pharmacological. According to previous research, foot massage is a non-pharmacological therapy that can reduce blood pressure for hypertension sufferers. This case study aims to provide an overview of the application of foot massage to reduce blood pressure in elderly people with hypertension in the Sewon 1 Bantul Community Health Center working area. This case study uses a descriptive method by obtaining a systematic and accurate picture of real events with data collection carried out by means of interviews, blood pressure checks, observation and documentation. The application of foot message therapy carried out for 3 days with a frequency of 1 time a day for a duration of 15 minutes can reduce the average blood pressure of clients from the first day to the third day before giving foot massage therapy by 145/105mmHg and after giving therapy by 110 /80mmhg. There was a decrease in the average systolic blood pressure before and after giving foot massage therapy by 21 and diastole by 18. The application of foot massage therapy can reduce blood pressure from the classification of stage 1 hypertension to pre hypertension. The classification used in this case study is according to JNC. Suggestion: It is hoped that families can apply foot massage techniques to elderly patients with hypertension.